MoleNet: An Underground Sensor Network for Soil Monitoring - Dede, Jens; Helms, Daniel; Förster, Anna (Electronic Communications of the EASST, 2021)
With the increasing digitalization worldwide, the demand of information also increases in all areas. MoleNet is a low-power sensing platform which is easy to assemble and use. It offers several options to monitor, for example, the soil moisture and temperature and visualize the data. Several researchers from different countries are currently working and improving MoleNet for different applications. This demo shows the main application of MoleNet: Monitoring soil conditions in a remote area, transmitting the data and visualizing the current status.